Application of istof-ii System in No-Anglo-Saxon Educational Context - Begoña De la Iglesia Mayol; María Rosa Rosselló Ramon (Universidad Autónoma de Madrid, 2018)
The objective of this study is to identify which schools and which teachers can be considered effective, based on an observation tool that evaluates the effectiveness of the school and the teacher. The International System for Teacher Observation and Feedback (istof-ii) was used in a non-Anglo Saxon educational context for the first time. Research techniques were used that combine qualitative (interviews with teachers and head teachers in the selected schools) and quantitative (observation protocol) analysis. Twenty-one teachers were observed teaching languages (Spanish, Catalan and English) and mathematics in 15 primary schools. The results showed negative links between the age and experience of the teachers and their practices and between the percentage of students at a low socio-economic level and the quality of teaching they receive. The study proves that an internationally valid observation system, such as the istof-ii, is a useful tool in in identifying effective practices and schools. Discussion concerns the importance of identifying and spreading effective centers and practices through international systems of assessment.